Haemoglobin D Ouled Rabah (beta 19[Bl] asn leads to lys) in a Tuareg tribe of the Southern Sahara. Issue 4 (August 1977) - Mauran-Sendrail, A; Lefevre-Witier,; Lehmann, H; Casey, R
Abstract : Haemoglobin Ouled Rabath found only once before in an Algerian has been discovered at high frequency in the Kel Kummer Tuaregs in Mali. The tribe represents a 'genetic isolate'.